Legal Consequences Of Mortgage Right Imposition On Uncertified Land (Letter C) In Case The Grantor Is Passed Away - Susilowati Susilowati; Yuniar Pradhana Mukti; Gunarto Gunarto (Jurnal Akta, 2018)
The purpose of this study is to know the implementation of the uncertified land as mortgage right (Letter C) and how the effect occurs in case that the grantor is passed away. This research was done with normative juridical approach. Technique of collecting legal material used literature study, while technique of data analysis was done with descriptive qualitative. The author found that UUHT provides an opportunity for owners of uncertified land rights to pledge their land rights in mortgage rights. It is mentioned in Article 10 Paragraph (2) of UUHT stating that if the object of mortgage rights in the form of land rights arising from the conversion of old rights that have been eligible to be registered but the registration has not been done, the granting of the mortgage shall be conducted simultaneously with the application of the right to (Letter C). On the other hand, the mortgagee has died and left the heirs, then there are several ways of settlement made by the bank, namely: If the credit has matured, then the credit is covered by credit insurance. If the credit has matured and the credit insurance has expired, it will be billed up to his heirs by approaching the family by offering loan interest rate relief. It is expected that the government through the National Land Agency can organize the process of land certification in a relatively short time so that it can support the economic activities of the community.Keywords: Mortgage Right; Uncertified Land; The Grantor Is Passed Away